Manifestasi Otologik Dari Penyakit Sistemik: Herpes Zoster Oticus (Hzo) - Nurul Milenia, Uni (Jurnal Syntax Fusion, 2022)
Herpes zoster oticus (HZO) or known as Ramsay Hunt-Syndrome is a collection of symptoms consisting of acute otalgia accompanied by the appearance of herpetic vesicles and facial paresis. The purpose of this paper is to summarize knowledge related to herpes zoster oticus and to find out the otologic manifestations of herpes zoster oticus that is clinical manifestations, management, complications and prognosis in patients with herpes zoster oticus. The method used in writing this literature review is literature review, using literature searching. Library search uses website-based search tools, namely Google, Google Scholar and NCBI. Free full text English and Indonesian publications. The total number of journals selected in this literature review is 6 journals. HZO is characterized by the appearance of a triad of Bell's palsy, ear pain and vesicles. If not treated immediately, it will result in a worse prognosis and various complications occur